The influence of industry-specific personal characteristics on consumer reactions to domestic vs. foreign comparative advertising in the American automobile market - William T. Neese; William Foxx; Dianne B. Eppler (Cogent Business & Management, 2018)
Many US households depend on jobs generated by foreign automobile production and marketing. Foreign vs. domestic comparative advertising influences consumer ethnocentric reactions, but what effect does it have on employees of these foreign automobile brands? We replicate and extend Neese and Haynie by analyzing industry-specific Cognitive (knowledge), Affective (judgment), and Conative (employment status) covariates. Hierarchy of Effects and CETSCALE means vary significantly across treatments when these covariates are included in a MANCOVA. Regression analysis demonstrates that Attitude toward the Brand, Attitude toward the Ad, and Conative predict Purchase Intentions for participants processing foreign comparative advertising.
Keywords: 650